Doing Business in Italy 2013 - World Bank; International Finance Corporation (World Bank and International Finance Corporation, Washington, DC, 2017)
Doing Business in Italy 2013 is a new subnational report of the Doing Business series. It measures business regulations and their enforcement across 4 indicators in 13 Italian cities: Bari (Apulia), Bologna (Emilia-Romagna), Cagliari (Sardinia), Campobasso (Molise), Catanzaro (Calabria), L'Aquila (Abruzzo), Milan (Lombardy), Naples (Campania), Padua (Veneto), Palermo (Sicily), Potenza (Basilicata), Rome (Latium), and Turin (Piedmont) and the indicator trading across borders in 7 ports: Cagliari (Sardinia), Catania (Sicily), Genoa (Liguria), Gioia Tauro (Calabria), Naples (Campania), Taranto (Apulia), Trieste (Friuli-Venezia Giulia). The cities were selected by the Department for Planning and Coordination of Economic Policy (DIPE) of the Presidency of the Council of Ministers of the Italian Republic. The cities can be compared against each other, and with 185 economies worldwide. Doing Business investigates the regulations that enhance business activity and those that constrain it. Regulations affecting 5 stages of the life of a business are measured at the subnational level in Italy: starting a business, dealing with construction permits, registering property, trading across borders and enforcing contracts. These indicators were selected because they cover areas of local jurisdiction or practice. The indicators are used to analyze economic outcomes and identify what reforms have worked, where and why. The data in Doing Business in Italy 2013 are current as of June 1st, 2012.